Advances in Human Error, Reliability, Resilience, and Performance Proceedings of the AHFE 2017 International Conference on Human Error, Reliability, Resilience, and Performance, July 17-21,2017, The Westin Bonaventure Hotel,Los Angeles, California, USA (Advances in Intelligent Systems and Computing,, 2018)
This book brings together studies broadly dealing with human error from different disciplines and perspectives. They concern human performance; human variability and reliability analysis; medical, driver and pilot error, as well as automation error; reports on root cause analyses; and the cognitive modeling of human error. In addition, they highlight cutting-edge applications in safety management, defense, security, transportation, process controls, and medicine, as well as more traditional fields of application. Based on the AHFE 2017 International Conference on Human Error, Reliability, Resilience, and Performance, held on July 17-21, 2017 in Los Angeles, California, USA, the book includes experimental papers, original reviews, and reports on case studies, as well as meta-analyses, technical guidelines, best practice and methodological papers. It offers a timely reference guide for researchers and practitioners dealing with human error in a diverse range of fields. .